Uncovering Moses Ben Sabbataï: A Fourteenth-Century Critic of Philosophers and Kabbalists - De Doncker, Ellen (UCO Press, 2021)
In his monograph "Moïse b. Sabbatai, lecteur juif du Livre des causes et adversaire de la Kabbale, en Italie, vers 1340", Jean-Pierre Rothschild introduces an important Jewish philosopher and the writings attributed to this medieval scholar. Through his intensive research and earlier studies, Rothschild has single-handedly saved Moses ben Sabbatai from oblivion. Rothschild now carefully presents the thinker, his writings, and his sources, providing the most extensive material for studies on Moses b. Sabbatail. Rothschild’s book also constitutes the main source for information on the Hebrew receptionof the Liber de causis.